Analisis Pemeriksaan MRI Pelvis Pada Kasus Kanker Serviks Di Instalasi Radiologi RSUP Persahabatan - Hildaimawanti Hildaimawanti; Ni Putu Rita Jeniyanthi; Triningsih Triningsih; I Kadek Sukadana (Pusat riset dan Inovasi Nasional, 2023)
The aim of this research is to find out the procedures for Pelvic MRI examinations in Cervical Cancer Cases at the Radiology Installation at Persahabatan Hospital, to find out the reasons for using T1W SPIR and to find out the reasons for using T2W SPAIR in Pelvic MRI examinations in cervical cancer cases. This type of research uses descriptive qualitative methods with a case study approach. Data collection methods are carried out through observation, interviews and documentation. Then data analysis was carried out using open coding charts and categorization tables, so that conclusions could be drawn. The results of this study indicate that the Pelvic MRI examination procedure in cases of cervical cancer at Persahabatan Hospital using contrast media requires special preparation, namely the patient fasting from eating fibrous foods 1 day before the examination, taking laxatives 12 hours before the examination, and checking urea creatinine. The patient is injected with 20 cc of ultrasonic gel in the rectum and vagina which functions as a marker. The purpose of using the T1W SPIR sequence is to compare enhancement before and after administration of contrast media. The use of T2W SPAIR in pelvic MRI examinations to assess pathological fluid by suppressing fat signals.